Quantifying mineral liberation by particle grade and surface exposure using X-ray microCT. (15th August 2018) - Reyes, F.; Lin, Q.; Cilliers, J.J.; Neethling, S.J.
Highlights: Methodology for extracting surface exposure and grade from densely packed particles from 3D images. 3D distributions of surface exposure for a given fragment size, grade and mineralogy can be obtained. The extent to which there is preferential breakage can be assessed for each mineral phase. Abstract: Liberation is a key driver in all mineral separation processes as it limits the maximum possible grade for a given recovery. In flotation, this is further complicated by the fact that it is surface exposure of the floatable minerals that determines the ultimate performance. Liberation, grade and surface exposure are commonly quantified using Scanning Electron Microscopy coupled to Energy Dispersive X-ray spectroscopy (SEM/EDX) analysis of polished sections. The intrinsically 2D nature of this technique can result in significant sampling errors and stereological effects that can affect the quantification of the ore's textural characteristics. X-ray microCT (XMT) is an imaging method that can non-invasively and non-destructively delineate ore fragments in 3D, thus providing an alternative method that eliminates the need for stereological corrections and readily provides surface exposure. A methodology and automated algorithm were developed for extracting this information from images of closely packed particles. By dividing these particles into classes based on both their surface exposure and grade, the extent to which there is preferential breakage of the particles can be assessed—an important consideration if sufficient surface liberation for good flotation performance is to be achieved at coarser particle sizes. Using low energy scanning simple 3D mineral maps can be obtained via XMT, allowing for the assessment of liberation and surface exposure for each mineral species. The methodology was tested on low grade porphyry copper ore as this is representative of the most commonly treated ore types for copper production.